Geronimo Stilton: The Kingdom of Fantasy #7: The Enchanted Charms (HC) - Stilton, Geronimo (Kingdom of fantasy, #7, 2015)
For the seventh time Geronimo Stilton finds himself in the Kingdom of Fantasy--this time Blossom, Queen of the Fairies, needs him to find the seven enchanted charms before the evil Wizard of the Black Pearl can get to them.